Nonlinear optical response and self-trapping of light in biological suspensions. Issue 1 (1st January 2020) - Gautam, Rekha; Bezryadina, Anna; Xiang, Yinxiao; Hansson, Tobias; Liang, Yi; Liang, Guo; Lamstein, Josh; Perez, Nicolas; Wetzel, Benjamin; Morandotti, Roberto; Chen, Zhigang
ABSTRACT: In the past decade, the development of artificial materials exhibiting novel optical properties has become a major scientific endeavor. One particularly interesting system is synthetic soft matter, which plays a central role in numerous fields ranging from life sciences, chemistry to condensed matter and biophysics. In this paper, we review briefly the optical force-induced nonlinearities in colloidal suspensions, which can give rise to nonlinear self-trapping of light for enhanced propagation through otherwise highly scattering media such as dielectric and plasmonic nanosuspensions. We then focus on discussing our recent work with respect to nonlinear biological suspensions, including self-trapping of light in colloidal suspensions of marine bacteria and red blood cells, where the nonlinear response is largely attributed to the optical forces acting on the cells. Although it is commonly believed that biological media cannot exhibit high optical nonlinearity, self-focusing of light and formation of soliton-like waveguides in bio-soft matter have been observed. Furthermore, we present preliminary results on biological waveguiding and sensing, and discuss some perspectives towards biomedical applications. The concept may be developed for subsequent studies and techniques in situations when low scattering and deep penetration of light is desired. GRAPHICAL ABSTRACT: